The Quality of Boer Goat Semen Preserved with Sugar Palm Juice - Muhammad Rizal; Muhammad Riyadhi; Abrani Sulaiman (Buletin Peternakan, 2018)
The objective of this study was to examine the effect of seminal plasma on viability of Boer goat spermatozoa and effectiveness of sugar palm juice as an alternative extender during preservation at 5ºC. Semen of two Boer goats were collected using an artificial vagina. Fresh semen were evaluated and divided in equal volume into four tubes. Semen in the first and second tubes diluted with 80% sugar palm juice + 20% egg yolk (P1) and Andromed (P2), respectively. Semen in the third and fourth tubes were centrifuged with 3,000 RPM for 20 minutes, and the supernatant removed. diluted with 80% sugar palm juice + 20% egg yolk (P3) and Andromed (P4), respectively. Diluted-semen were preserved in refrigerator at 5oC, and quality of the spermatozoa including motile spermatozoa (MS), live spermatozoa (LS), and intact plasma membrane (IPM) were evaluated every day for four days. Results of this study showed that at day-2 preservation, mean percentages of MS, LS, and IPM for P2 (72, 83.4, and 83.4%), P3 (72, 82.6, and 82.2%), and P4 (72, 83, 83.8%) were significantly (P<0.05) higher than P1 (3, 24.8, and 25.2%). At day-3 preservation, mean percentages of MS, LS, and IPM for P2 (57, 65.6, and 69.6%) was significantly (P<0.05) higher than P3 (21, 34.8, and 31.8%), P4 (22, 33.6, and 31.2%), and P1 (0, 0, and 0%). In conclusion, semen of Boer goat to be preserved with extender containing egg yolk should be removed seminal plasma. Sugar palm juice containing egg yolk could be used as an extender for Boer goat semen, but should be applied in the AI program immediately after the semen is diluted.